PEMBELAJARAN KRITIS DI PESANTREN: Studi Kasus di Pesantren Pertanian Darul Fallah Bogor - Sarwenda Sarwenda (Faculty of Educational Sciences, Syarif Hidayatullah State Islamic University, 2014)
The result of this research reveals that critical thinking skills possessed by the students in the pesantren has been developed through several learning approaches implemented during learning process in the pesantren. Among the approaches are critical awareness on the study of classical books (bahtsul masâil), discussion and debate in which students and teachers are equal in presenting ideas (cooperative and collaborative strategies are also embedded in this approach), and problem solving approach in which contextual issues are posed and solved. While creating students to be critical, such approaches were found to preserve students’ moral attitude to the teachers that has been skeptically seen will be deminished. DOI: 10.15408/tjems.v1i2.1265